PRACTICAL PACKET ANALYSIS : using Wireshark to solve real-world network problems - Sanders, Chris (No Starch Press, 2017)
Provides information on ways to use Wireshark to capture and analyze packets, covering such topics as building customized capture and display filters, graphing traffic patterns, and building statistics and reports